(3WHbGJ GdNhGU Cgd GdUOb hGdENdGUs - (3GdRHjOj , CMeO Hf CMeO Hf YHO GddWja GdTQLj, TgGH GdOjf,J (B893 (3g` s ((3Ydhi Hf LYaQ Hf Ydhi Hf YHO Gddg GdSbGa s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd HLRjd GdehGgH hGdYWGA , CeG HYO , aEfi hbaJ Ydi LedI ef GdcJH GdeUfaI ai PcQ ChdjGA Gddg JYGdi s
(3BNQgG (B:s
(3gPG BNQ eG JjSQ LejYg ef PcQ gDdGA GdSGOI , hCfG CJhSd Hge Edi Gddg JYGdi Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3fSNI CNQis
(3cJHJ QDhS GdJQGLe hHYV GdYfhGfGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs